2013
DOI: 10.1002/adom.201200009
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial‐Based Two Dimensional Plasmonic Subwavelength Structures Offer the Broadest Waveband Light Harvesting

Abstract: Metamaterials, which are composed of metallic and dielectric subwavelength structures arranged in periodic array, are artifi cial materials with the permittivity or permeability less than that of vacuum or with negative values unattainable in nature. [1][2][3] Due to their unique electromagnetic properties, metamaterials have been widely used in many applications, such as sensors, superlenses, miniature antennas, and invisible cloaks. [4][5][6][7] Recently, metamaterial-based perfect absorbers have been attrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(75 citation statements)
references
References 34 publications
1
74
0
Order By: Relevance
“…Moreover, due to the effects of multiple metal/dielectric thin films and the truncated cone shapes, the proposed metamaterial structure can greatly suppress the reflection of light by effectively providing a graded transition of refractive index, and thus acts as an ultra-broadband multilayer antireflection coating as well. 19 Thus, the present simulation results demonstrate that the broadband absorber structure have excellent transmissivity in low-frequency.…”
Section: Numerical Analysis and Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Moreover, due to the effects of multiple metal/dielectric thin films and the truncated cone shapes, the proposed metamaterial structure can greatly suppress the reflection of light by effectively providing a graded transition of refractive index, and thus acts as an ultra-broadband multilayer antireflection coating as well. 19 Thus, the present simulation results demonstrate that the broadband absorber structure have excellent transmissivity in low-frequency.…”
Section: Numerical Analysis and Discussionsupporting
confidence: 56%
“…Therefore, the absorption of multilayered structure is formed not only by the electric resonance but also by the magnetic resonance. 19 Figure 6 (b) shows the y-component electric field at the metal/ dielectric interface, it can be seen that the magnetic field and electric field were concentrated in dielectric layers obviously, the strong absorption mostly root in dielectric loss of dielectric layers. It should be mentioned that the induced magnetic field is located at the center while the induced electric field is formed at the sides.…”
Section: Numerical Analysis and Discussionmentioning
confidence: 99%
“…Previously, in order to obtain a broad band response, multiple modes resonant at difference wavelengths are combined either transversely or longitudinally to form a super unit cell. [60][61][62][63][64] Similarly, by composing two coupled rectangular dielectric resonator within one unit cell ( Figure 1 g), silicon metasurface has been demonstrated to enable defl ecting or focusing multiply wavelengths achromatically. [ 65,66 ] It further broadens the capabilities of metasurfaces and suggests an unparalleled approach to circumvent the stubborn limitation of existing optical elements.…”
Section: Achromatic Metasurfacesmentioning
confidence: 99%
“…dielectric in one direction and metallic in other directions), which is promising for a variety of applications, including three-dimensional indefinite cavities 26 , spontaneous emission enhancement 22,53 , active nanoplasmonic devices 27,28 , etc. Recently, an interesting concept was proposed to realize an on-chip ultra-broadband and tunable super absorber in near-IR, mid-IR to microwave domain [29][30][31] using patterned HMM waveguide taper arrays constructed by multilayered metal/dielectric thin films. The physical mechanism of this intriguing ultrabroadband absorption was attributed to slow light modes confined in HMM waveguide tapers, leading to the enhanced light-matter interaction and therefore, strong/perfect absorption of the light.…”
mentioning
confidence: 99%
“…For most periodic grating structures, their optical properties are usually sensitive to the periodicity of patterns. In previously reported theoretical design [29][30][31] , the period of the array was generally selected based on the bottom width of the HMM waveguide taper. It has not been revealed that how the period selection will affect the absorption properties of the patterned HMM films.…”
mentioning
confidence: 99%